2017
DOI: 10.1007/s11999-016-5177-5
|View full text |Cite
|
Sign up to set email alerts
|

Periacetabular Osteotomy Provides Higher Survivorship Than Rim Trimming for Acetabular Retroversion

Abstract: Background Acetabular retroversion can cause impaction-type femoroacetabular impingement leading to hip pain and osteoarthritis. It can be treated by anteverting periacetabular osteotomy (PAO) or acetabular rim trimming with refixation of the labrum. There is increasing evidence that acetabular retroversion is a rotational abnormality of the entire hemipelvis and not a focal overgrowth of the anterior acetabular wall, which favors an anteverting PAO. However, it is unknown if this larger procedure would be ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 63 publications
2
59
0
2
Order By: Relevance
“…[93][94][95] To address this deformity, an acetabular reorientation procedure is the rational option. According to Zurmühle et al, 96 it yields better long-term results than isolated rim trimming (►Fig. 8).…”
Section: Pincer Impingementmentioning
confidence: 99%
“…[93][94][95] To address this deformity, an acetabular reorientation procedure is the rational option. According to Zurmühle et al, 96 it yields better long-term results than isolated rim trimming (►Fig. 8).…”
Section: Pincer Impingementmentioning
confidence: 99%
“…42 A retrospective study proved that anteverting PAO was superior to hip surgical hip dislocation with rim trimming after ten-year follow-up (79.1% vs 23.0%, p = 0.0002). 45 …”
Section: Acetabular Retroversion With Fai Treated With Reverse Paomentioning
confidence: 99%
“…61,62 Depending on the severity of the deformity, an impingement-free range of motion can be restored with acetabular rim trimming or acetabular reorientation. 63,64 Until recently the assessment of FAI mainly focused on proximal femoral head morphology, acetabular coverage and version. However, it was shown that femoral torsion considerably affects the impingement-free range of motion 65,66 and that severely abnormal femoral torsion may be present in one of six hips undergoing an MRI of the hip.…”
Section: Impingement Morphologiesmentioning
confidence: 99%